2008
DOI: 10.1186/1471-2229-8-78
|View full text |Cite
|
Sign up to set email alerts
|

Variation in DNA methylation patterns of grapevine somaclones (Vitis vinifera L.)

Abstract: Background: In traditional vine areas, the production should present a typicity that partly depends on the grapevine variety. Therefore, vine improvement is considered difficult because of the limited choice in the natural variability of the cultivars within the limits of their characteristics. A possibility to circumvent this problem is the use of somatic variability. In vitro somatic embryogenesis and organogenesis can lead to genotypic and phenotypic variations, described as somaclonal variation, that could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
82
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 37 publications
3
82
0
Order By: Relevance
“…Similarly, low levels of methylation variation were found in freesia somatic seedlings derived from short-term cultures (Gao et al 2010) and pea long-term multiple shoot cultures (Smýkal et al 2007). Many studies with methylation-sensitive molecular markers that reported a high level of epigenetic variation reported no effect on phenotype or morpho-agronomic traits (Bednarek et al 2007;Li et al 2007;Schellenbaum et al 2008;Fiuk et al 2010). Methylation changes contribute poorly to global estimations when they do not occur at high frequencies (Smulders and Klerk 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, low levels of methylation variation were found in freesia somatic seedlings derived from short-term cultures (Gao et al 2010) and pea long-term multiple shoot cultures (Smýkal et al 2007). Many studies with methylation-sensitive molecular markers that reported a high level of epigenetic variation reported no effect on phenotype or morpho-agronomic traits (Bednarek et al 2007;Li et al 2007;Schellenbaum et al 2008;Fiuk et al 2010). Methylation changes contribute poorly to global estimations when they do not occur at high frequencies (Smulders and Klerk 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Somaclonal variations arise from multiple genetic causes, including chromosome number changes (polyploidy and aneuploidy), chromosomal structural rearrangements, gene mutations, gene copy number changes, and activation and transposition of transposable elements (Lee and Phillips 1987;Lee 1988;Bairu et al 2011). Somatic variation could also result from epigenetic changes or pre-existing mutations in the explants used in cell and tissue culture (Alatzas and Foundouli 2006;Schellenbaum et al 2008;Bairu et al 2011).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The variation in gene expression is believed to be mediated by epigenetic mechanisms involving methylation of DNA and chromatin modifications. Shifts from parental methylation states have been observed in many cell cultures and regenerated plants at both global and local levels (Kaeppler and Phillips, 1993;Smulders et al, 1995;Olhoft and Philips, 1999;Jaligot et al, 2000;Kubis et al, 2003;Schellenbaum et al, 2008). Alleviation of silencing of ribosomal genes (Komarova et al, 2004;Koukalova et al, 2005), increased transposon activity (Hirochika, 1993;Grandbastien, 1998), and activation of cell cycle-controlling genes (Williams et al, 2003) were reported in studies linking changes in DNA methylation with changes in expression patterns.…”
mentioning
confidence: 99%